04 Methods of Teaching Spanish as Foreign Language To Albanian Students - Viola BITI GJYLI (Association of Social and Educational Innovation, 2016)
Language teaching is in a continuous developing process in the auditorium and outside it. It includes various educational and linguistic disciplines which may change and be put into practice through methodological skills of teaching and learning of languages. As Richterich mentions: "One of the main features of teaching language, is undoubtedly its immediate adjustment in some difficult notions to reduce this problem and using them in more plentiful linguistic and educational interpretations (Richtérich, 1994, 113). Nowadays, various proposals have been submitted, in order to change traditional patterns of teaching and to improve the exercises and activities considered old. Traditional teaching is adorned and enriched by other objectives such as: the development of logical thinking, the ability to summarize texts and increase the ability of understands another language and its literary texts.